2021
DOI: 10.1111/jace.18023
|View full text |Cite
|
Sign up to set email alerts
|

Relation between crystal structure and lattice oxygen content of sintered reaction‐bonded silicon nitride

Abstract: When reaction‐bonded silicon nitride containing MgO/Y2O3 additives is sintered at three different temperatures to form sintered reaction‐bonded silicon nitride (SRBSN), the thermal conductivity increases with sintering temperature. The β‐Si3N4 (silicon nitride) crystals of SRBSN ceramics were synthesized and characterized to investigate the relation between the crystal structure and the lattice oxygen content. The hot‐gas extraction measurement result and the crystal structure obtained using Rietveld analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The thermal conductivity increased with increasing the nitridation temperature. Thermal conductivity is not only affected by microstructures such as porosity and amounts, distribution and crystalline state of grain boundary, but also the lattice oxygen in Si 3 N 4 grain because an oxygen impurity dissolved in the β‐Si 3 N 4 grain creates phonon‐scattering silicon vacancies that decrease the thermal conductivity of Si 3 N 4 ceramics 8,12,14,28,32,33 . As the microstructures were composed of almost the same morphologies regardless of the nitridation temperature, the increase of thermal conductivity should be due to the influence of the amount of lattice oxygen in Si 3 N 4 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal conductivity increased with increasing the nitridation temperature. Thermal conductivity is not only affected by microstructures such as porosity and amounts, distribution and crystalline state of grain boundary, but also the lattice oxygen in Si 3 N 4 grain because an oxygen impurity dissolved in the β‐Si 3 N 4 grain creates phonon‐scattering silicon vacancies that decrease the thermal conductivity of Si 3 N 4 ceramics 8,12,14,28,32,33 . As the microstructures were composed of almost the same morphologies regardless of the nitridation temperature, the increase of thermal conductivity should be due to the influence of the amount of lattice oxygen in Si 3 N 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Thermal conductivity is not only affected by microstructures such as porosity and amounts, distribution and crystalline state of grain boundary, but also the lattice oxygen in Si 3 N 4 grain because an oxygen impurity dissolved in the β-Si 3 N 4 grain creates phonon-scattering silicon vacancies that decrease the thermal conductivity of Si 3 N 4 ceramics. 8,12,14,28,32,33 As the microstructures were composed of almost the same morphologies regardless of the nitridation temperature, the increase of thermal conductivity should be due to the influence of the amount of lattice oxygen in Si 3 N 4 . Kitayama et al 32 reported that the thermal conductivity of Si 3 N 4 ceramics increased from 58.8 to 99.1 W/(m K) with decreasing the oxygen contents from .400 to .058 wt.% by increasing the amount of Y 2 O 3 additives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations